2017
DOI: 10.1111/jvp.12432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspirin dose escalation on platelet function and urinary thromboxane and prostacyclin levels in normal dogs

Abstract: Title of Study: Effects of aspirin dose escalation on platelet function and urinary thromboxane and prostacyclin levels in normal dogs Pages in Study: 75Candidate for Degree of Master of Science Eight dogs were enrolled in a randomized, cross-over study that used optical aggregometry and a platelet function analyzer to evaluate platelet function before and after the administration of 5 aspirin dosages: 0.5 mg/kg q24h, 1 mg/kg q24h, 2 mg/kg q24h, 4 mg/kg q24h and 10 mg/kg q12h. Urine 11-dehydro-thromboxane-B2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…A previous study performed at this institution indicated that 1 mg/kg/d was the lowest dosage that inhibited platelet function as assessed by PFA‐100 and optical aggregometry . However, a recent report suggested that an aspirin dosage of 2 mg/kg may be more reliable for platelet inhibition . In that study, the 2 mg/kg dosage resulted in a mean decrease in maximum amplitude of 81.3% with turbidimetric aggregometry and a CT >300 seconds in 62.5% of dogs with PFA‐100, compared to 41.3% and 25%, respectively, for an aspirin dosage of 1 mg/kg.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study performed at this institution indicated that 1 mg/kg/d was the lowest dosage that inhibited platelet function as assessed by PFA‐100 and optical aggregometry . However, a recent report suggested that an aspirin dosage of 2 mg/kg may be more reliable for platelet inhibition . In that study, the 2 mg/kg dosage resulted in a mean decrease in maximum amplitude of 81.3% with turbidimetric aggregometry and a CT >300 seconds in 62.5% of dogs with PFA‐100, compared to 41.3% and 25%, respectively, for an aspirin dosage of 1 mg/kg.…”
Section: Discussionmentioning
confidence: 86%
“…More recently LTA has been used alongside the PFA to investigate the optimum dose of aspirin in dogs (McLewee et al . ).…”
Section: Specific Tests Of Platelet Functionmentioning
confidence: 97%
“…As such, it may have clinical utility for monitoring response to treatment. However, it is also suggested that, compared to optical aggregometry, the PFA is less reliable in determining drug responsiveness and can markedly overestimate the degree of aspirin resistance (Gaál et al 2007, Dudley 2013, Haines et al 2016, Ho et al 2016, McLewee et al 2017, Saati et al 2017 Clancey et al 2009aClancey et al , 2009b, as well as dogs with chronic kidney disease and endotoxaemia (Yilmaz et al 2005, Dudley et al 2017. The PFA has also been used to diagnose Scott syndrome (Brooks et al 2009).…”
Section: Assessment Of Platelet Adhesion Under Shear Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin is still a reasonable drug for thromboprophylaxis, but PFT and future studies are indicated. Additionally, dogs receiving aspirin could have had further assessment of response to treatment in addition to PFT such as measurement of serum salicylate or urinary 11‐dehydro‐thromboxane B 2 concentrations . Another reason dogs with aspirin were included despite small numbers was because PA appeared clinically useful when assessing a patient with a suspected severe vascular event.…”
Section: Discussionmentioning
confidence: 99%